Introduction: Towards a global sociology of care and care work. (July 2018) - Aulenbacher, Brigitte; Lutz, Helma; Riegraf, Birgit
Although care and care work have always formed a theme of fundamental social significance, neither has had much social recognition nor sociological attention commensurate with this importance. In this Current Sociology monograph we want to move the discussion forward towards a global sociology of care and care work. The contributions focus on both theoretical and empirical studies about care relations and their global interrelations. To shed light on the dynamics that characterise the social organisation of care and care work, the monograph has been structured around three significant tendencies in the international sociology of care: (a) the marketisation and the de-commodification of care and care work; (b) the transnationalisation of labour and policies; and (c) new forms of governance and social statehood. The articles in this monograph present state of the art research reflecting on the care-situation, -arrangements and -regimes all over the globe.